Business management of Homeomed Sdn. Bhd. – A case study of a local SME (Global Business Management Review (GBMR), 2022)
Homeopathy is categorized under Traditional and Complimentary Medicine (TCM) and is an underrated business both by the government and the public. There is less support by the government from the perspective of acknowledgement, nationwide publication, and validation on homeopathy as an important complimentary medicine.   To escalate the issue further, homeopathy practitioners have been practicing homeopathy in a traditional manner and disconnected with the principles and concepts of business management and administration. Homeomed Sdn. Bhd. (Homeomed) is one of the homeopathy companies; operating in Bukit Beruang, Melaka; they had almost ceased the business few times due to high operational cost and the effects of Covid-19 pandemic. They were experiencing the classical business challenges for SME of having a “bulk business issues” in all aspects of business management due to incompetency or ignorance or both. The main tasks here is to identify the gaps from a business point of view and to propose a few improvement recommendations focusing on operation, marketing, sales, human resource, finance, supply chain and customer service. During the implementations of new business techniques and approaches, main performance indicators such as revenue, number of patients, inquiries and customer satisfaction were measured to reflect Homeomed’s competitiveness. The data collected are analysed and studied for further improvement initiatives. The data collected are analysed and studied for further improvement initiatives. A total of five main problem areas were identified and solutions were implemented in 5 stages with all of it deriving positive outcomes.